Sviluppo come? Contributo per uno stato dei lavori sulle tecnologie appropriate - Ciuffoli, Massimo (L’Uomo società tradizione sviluppo, 2019)
The present essay is a guide to and examination of direct and intermediate technologies With reference to some basic principles of economic theory. Because of the complexity of the subject, the author chose to establish reference points for future development rather than attempt a wide-ranging anthological treatment of recent studies of the subject. Future essays in L'Uom0 Will help bring into focus the more urgent problems involved in Italian technical cooperation and assistance in other countries. The essay examines the problem of presentday technology in the Wider context of initiating real development in backward areas and sees technical cooperation as a decisive factor in introducing appropriate levels of technology in emerging countries, With the primary objectives of conserving natural resources and initiating self-development from the grass-roots level up. The essay ends With observations on new research and study in Italy connected. with programs that adopt logically appropriate choices of technology.